2008
DOI: 10.17744/mehc.30.1.2585916185422570
|View full text |Cite
|
Sign up to set email alerts
|

Using to Numb the Pain: Substance Use and Abuse Among Lesbian, Gay, and Bisexual Individuals

Abstract: The purpose of this study was to examine the relationship between heterosexist events, internalized homophobia, and substance use and abuse among 824 lesbian, gay, and bisexual (LGB) individuals. Participants completed the Schedule for Heterosexist Events (SHE), Internalized Homophobia Scale (IHP), Alcohol Use Disorders Identification Test (AUDIT), and the Drug Abuse Screening Test (DAST). A MANCOVA with age as a covariate and sexual orientation as a cofactor indicated there were significant differences in how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 47 publications
(59 reference statements)
6
60
1
2
Order By: Relevance
“…Notably, however, the existing body of research that explores differences between nonexclusive and exclusively same-sex attracted/identified populations is inconsistent. Some researchers, for example, have found that LG individuals experience greater conflict about their sexuality (Moore & Norris, 2005) as well as higher levels of IH than bisexually identified persons (Weber, 2008). Contrary to existing evidence that suggests bisexual individuals experience greater psychological distress than their LG counterparts (Jorm, Korten, Rodgers, Jacomb, & Christensen, 2002), our results did not demonstrate significant differences in depression scores between NSS attracted participants and those who identified as LG.…”
Section: Sexual Identitycontrasting
confidence: 99%
“…Notably, however, the existing body of research that explores differences between nonexclusive and exclusively same-sex attracted/identified populations is inconsistent. Some researchers, for example, have found that LG individuals experience greater conflict about their sexuality (Moore & Norris, 2005) as well as higher levels of IH than bisexually identified persons (Weber, 2008). Contrary to existing evidence that suggests bisexual individuals experience greater psychological distress than their LG counterparts (Jorm, Korten, Rodgers, Jacomb, & Christensen, 2002), our results did not demonstrate significant differences in depression scores between NSS attracted participants and those who identified as LG.…”
Section: Sexual Identitycontrasting
confidence: 99%
“…-Drug and alcohol use is caused in part due to internalized homophobia (Cheng, 2003). -Counselor education programs should address sexual identity development considering that acceptance of self is a contributing factor of substance use (Weber, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…It is estimated that sexual minorities use alcohol and drugs seven times more frequently than heterosexuals (Cochran, Stewart, Ginzler, & Cauce, 2002;Collins, Rocco, & Bryant, 2014;Gedro, 2014;Woodford et al, 2012). Having a drug or alcohol abuse disorder among sexual minorities has been closely associated to the negative experiences and climate they are exposed to (Weber, 2008 (Lee, 2015).…”
Section: Alcoholism and Drug Abusementioning
confidence: 99%